Political Competition with Endogenous Party Formation and Citizen Activists - Emanuel Hansen (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
The paper studies political competition between endogenously formed parties instead of independent candidates. Party formation allows policy-motivated citizens to nominate one of their fellow party members as their candidate for a general election and to share the cost of running in this election. Thus, like-minded citizens are able to coordinate their political behavior in order to improve the policy outcome. The paper focuses on political equilibria with two active parties, and investigates the properties of stable parties and the policy platforms offered in equilibrium. The platforms of both parties can neither be fully convergent as in the median voter model (Downs 1957) nor extremely polarized as in the citizen candidate model (Besley & Coate 1997). In the benchmark case of full electoral certainty, a unique political equilibrium with positive platform distance exists. Endogenous party formation thus eliminates a major weakness of the citizen candidate model, the extreme multiplicity of equilibria. The model remains tractable, and the qualitative results are shown to be robust under the assumption of electoral uncertainty, where vote results cannot be perfectly predicted.
Keywords: D72; D78; C72; 330